2022
DOI: 10.1038/s41598-022-23313-7
|View full text |Cite
|
Sign up to set email alerts
|

Low levels of hemoglobin associate with critical illness and predict disease course in patients with ANCA-associated renal vasculitis

Abstract: Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a small vessel vasculitis often leading to critical illness by multi-organ failure. Data for patients with specifically ANCA-associated renal vasculitis requiring intensive care unit (ICU) supportive care are limited and have mainly focused on long-term renal and overall outcome. Particularly, data on critical illness during the initial course of disease are scarce and remain poorly determined. Therefore, the purpose of this retrospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Severe anemia that was not consistent with renal failure and hemoptysis indicated that the mechanism of anemia in patients with AAV was much more complex. Low levels of hemoglobin had a negative effect on short-term prognosis in AAV patients [21]. Previous studies had suggested that the pathogenesis of anemia in AAV with renal injury differed from that of other immune-related diseases, and the factors that might contribute to the development of anemia in AAV patients have not been fully clarified yet.…”
Section: Discussionmentioning
confidence: 97%
“…Severe anemia that was not consistent with renal failure and hemoptysis indicated that the mechanism of anemia in patients with AAV was much more complex. Low levels of hemoglobin had a negative effect on short-term prognosis in AAV patients [21]. Previous studies had suggested that the pathogenesis of anemia in AAV with renal injury differed from that of other immune-related diseases, and the factors that might contribute to the development of anemia in AAV patients have not been fully clarified yet.…”
Section: Discussionmentioning
confidence: 97%
“…We here directly compare the scoring system with retrospective data about PLEX treatment in our own clinical practice and according to current recommendations in patients presenting with a serum creatinine levels above 5.7 mg/dL (500 μmol/L) and/or requirement of KRT in a cohort of 53 AAV patients with RPGN confirmed by kidney biopsy, detailed information about critical illness in this patient cohort has recently been described ( 14 16 ).…”
Section: Methodsmentioning
confidence: 99%
“…The Birmingham Vasculitis Activity Score (BVAS) and the Simplified Acute Physiology Score II (SAPS II) were calculated as previously described [43,44]. The state of critical illness (CI) was defined as recently described [42,45]. Laboratory data assessment encompassed whole blood cell counts (WBC) including hemoglobin levels; platelet and leukocyte counts; and serum levels of inflammatory markers, such as C-reactive protein (CRP), ferritin, haptoglobin, procalcitonin (PCT) and albumin; serum creatinine and blood urea nitrogen (BUN) levels at admission; iron; lactate dehydrogenase (LDH); aspartate amino transferase (AST); alanine amino transferase (ALT); and alkaline phosphatase (AP).…”
Section: Study Population and Data Assessmentmentioning
confidence: 99%